TEXAS: S&U Tax: Bookkeeper's Data Processing Services Taxable (State Tax Review, 2006)
According to Letter No. 200607779L from the Texas Comptroller of Public Accounts, when a bookkeeper merely enters data and records that are compiled or created by a client and does not analyze, review, or modify the results or apply his or her knowledge of accounting principles and tax laws, the services are subject to Texas sales and use tax as data processing services when they are performed using a computer.